Simulation model of Power Quality provider - Venkatachalam, P.A.; Chandrasekaran, K.; Mohd Noh, Karsiti; Rama Rao, K.S. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.